Analisa Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Kacamata Faiz Optical Tahun 2022 - Sari, Dian Leila (LPPM Universitas Dharma Andalas, 2022)
This study examines the role of marketing strategy management in increasing the sales volume of glasses at Faiz Optical in 2021 This study uses descriptive qualitative methods with interview techniques, and documentation is carried out to obtain data from the head office and buyers. The focus of this research is how to apply marketing strategymanagement to increase sales volume at Faiz Optical. The results of the study indicate that the management of marketing strategies which include 1). Segmentation, 2). Targeting, 3). Positioning, 4) Marketing Mix and 5). Timing strategy. The results above conclude that the implementation of marketing strategies in increasing sales volume is currently optimal in the components of segmentation, targeting, positioning, marketing mix, and timing strategies, so as to increase revenue at Faiz Optical.